A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea - Costa, Gabriele; Pansini, Maurizio; Bertolino, Marco (Zootaxa, 2019)
The use of ROVs has greatly enhanced the possibility of obtaining information on living deep sponge communities (Bertolino et al. 2015). The aim of this work is to describe a new Mediterranean species, Antho (Plocamia) sarasiri sp. nov. (Microcionidae Carter, 1875), characterized by dumbbell spicules making up the framework of the choanosomal skeleton (Van Soest et al. 2013). Samples were collected by ROV during an oceanographic survey in September 2012 on board of the R/V ‘Astrea’ (ISPRA) in “Secca P.ta Fetovaia” (42°43’29.54”N 10° 9’31.64”E) (Elba Island, Tyrrhenian Sea) at 70 m depth. We compared our sample with additional material collected by Sarà & Siribelli (1960, 1962).